Moralidade e trapaça: um estudo com crianças de 5 e 10 anos - Pessotti, Alice Melo (2010)
This research aims to investigate, in a psychogenetic perspective, the cheating act regarding the relation between the hypothetical trial, the observation of the action and the trial of the action itself of children in a situation of games which rules are involved, based on Piaget’s Theory. 40 children of two private schools of Linhares city – ES participated of this research aged between 5 and 10 years old, equally distributed according to the age and gender. This research was done with the following instruments being utilized: a story and an interview guide involving the cheating act in the Tic Tack Toe game; the Face to Face game and an interview guide posterior to the Face to Face game. The research was done in three steps: (a) hypothetical trial regarding the cheating act, (b) observation of the cheating’s action and (c) trial regarding the cheating’s action. The results permitted us to observe, regarding the hypothetical trial about the cheating act, that from the point they were requested to establish a trial that regards the narrated attitude, the totality of participants said that the cheating attitude was wrong, being the greatest number of justifications mentioned among children aged 5 which was the one of ‘circular arguments’. On the other hand, the category cited most times by the participants aged 10 was ‘disobeyed the rules of the game’. Concerning the observation, it was possible to notice that, during the absence of the experimenter, the cheating occurred more among children aged 5 than among the ones aged 10 years old. On the contrary, in the experimenter’s presence, it wasn’t verified relevant difference in cheating’s frequency between the two ages. Besides, it was found a variety of behaviors in order to cheat. Regarding the relation of the trial which concerns the action of the cheating, it is noted that, when asked indirectly about the action, the children aged 5 years old mention more frequently the cheating matter. Likewise, when asked directly about the attitude kept during the experiment, more children aged 5 said that they cheated than the ones aged 10 years old. Through these results, it was possible to notice that the children know that to cheat is not correct, but many cheat and few admit it, especially among the older ones. This way, this research contributes to the morality’s study because, when it demonstrates the importance of the action’s dimension, it can offer subsidies for a project of moral education.